Proximate, Phytochemical Analysis and Pharmacological Profile of Cassia Torra Native to Zuru Town, Kebbi State Nigeria - Garba, Aliyu; Usman Rufai Fakai (MultiTech Publisher, 2023)
Cassia tora, is commonly found in Nigeria, it’s annual shrub which grows in a wild land. The plant and its different parts are used for their nutritional and medicinal purposes. In the present study, an attempt was made to investigate nutritional contents, phytochemical analysis and medicainal evaluation of Cassia tora. The crude powder extracts of the leaves of the plants were taken for the study. The phytochemical Screening was done for the selected plants. Phytochemistry of the plant reveals that Cassia tora contains anthraquinones, protein, carbohydrates, saponins, glycosides, fixed oils and fats. Several chemical contents such asnaphthopyrone glycosides, flavonoids, glycosides, anthraquinone, etc. have beenseparated from this plant. The plants has been found to have hepatoprotective, antigenotoxic, antipsoriatic, antinociceptive, immunostimulatory, anticancerous, antifeedant, larvicidal, antiproliferative, hypolipidemic, antimutagenic activity. It also has a property of mild laxative and diuretics so can be used in constipation, dyspepsia and flatulence. Its decoction is used for healing and washing of wounds.